Principles of protein-protein association - Erickson, Harold P. (IOP (Series). Release 6., 2019)
Protein-protein associations are fundamental to biological mechanisms, creating a need for a book that covers the basic principles of protein-protein association. This book has been developed from lectures given to graduate students in cell and molecular biology. The general principles are accompanied by guided reading of informative classic papers. This book should be useful for faculties organizing similar classes, and also for students and researchers who wish to learn on their own. Part of the / Biophysical Society series.